Food resilience and adaptation on the move: the importance of fostering studies on the Romani local knowledge systems - Andrea Pieroni; Naji Sulaiman; Mousaab Alrhmoun (Journal of Ethnobiology and Ethnomedicine)
Abstract This analysis explores the food local knowledge of the Romani people in Italy, one of the most significant and historically marginalised ethnic groups in Europe. Despite their centuries-long presence across European countries, the Romani community’s culinary and herbal practices have often been overlooked. A preliminary study on Romani domestic food and home (plant) remedies was conducted via 106 interviews in Turin, Rome, and Naples during the past fifteen years among urban Romani community members (who migrated to Italy from Romania and Serbia approximately three decades ago). By examining Romani’s local food knowledge systems, this research highlights the importance of food ritual practices for preserving identity, fostering resilience, and bridging cultural divides; however, the data also show the plastic adaptability of Romani practices. Most quoted herbal items overlap the ones of the Balkan cultures where they lived together for centuries (Romanians and Serbs). The presented preliminary data insights into how the Romani diaspora in Italy has navigated cultural, economic, and social challenges through sophisticated mimicry and constant adaptation to new environments and cultures. Further understanding the Romani food ecological perceptions and ethnobotanical knowledge may be essential for improving social cohesion, challenging stereotypes, recognising the community’s valuable contributions to European cultural diversity and, in general, building a more inclusive ethnobiology.